(429) بعض النماذج لمشكلة النقل غير التقليدية وطرق حلها Some examples of the problem of non-traditional transportation and ways to solve it - محرم الحداد (معهد التخطيط القومى, 2026)
تتناول هذه المذكرة مجموعة من النماذج الرياضية المتقدمة لـ "مشكلات النقل غير التقليدية"، والتي تتجاوز النماذج البسيطة لتشمل قيوداً واقعية ومعقدة (pp. 1-2). يستعرض البحث نماذج النقل التي تتضمن قيوداً على أقصى أو أدنى كمية يمكن نقلها، وكيفية تحويلها إلى مشكلات نقل تقليدية لسهولة حلها، مع تقديم نموذج خاص لنقل "السلع غير المتجانسة" (مثل المنتجات البترولية المختلفة) التي تشترك في طاقة استيعابية إجمالية واحدة، مبيناً كيفية صياغتها رياضياً وتطبيقها على سياسات التصدير المثلى لتقليل التكاليف الإجمالية، كما يغوص الملف في الجوانب التخطيطية واللوجستية من خلال نموذج "النقل على مراحل" (من الإنتاج للمخازن ثم للمستهلك) ونموذج "اختيار المواقع المثلى للمصانع" (Location Problem) لدعم مشروعات التعمير، مع مراعاة طاقات التشغيل المتاحة (pp. 2, 9, 12). ويختتم البحث بتقديم نموذج عملي لشركات النقل داخل المدن يهدف إلى "تقليل وقت سير الوحدات فارغة" إلى أدنى حد ممكن، مستخدماً مصفوفات الأبعاد والمسافات بين الجراجات وأماكن الشحن والتفريغ للوصول إلى برنامج عمل يومي يحقق أقصى كفاءة اقتصادية لأسطول النقل. This memorandum addresses a set of advanced mathematical models for "non-traditional transport problems," which go beyond simple models to include realistic and complex constraints. The research reviews transport models that include constraints on the maximum or minimum quantity that can be transported, and how to transform them into traditional transport problems for ease of solution. It also presents a special model for transporting "heterogeneous goods" (such as different petroleum products) that share a single total carrying capacity, showing how to formulate it mathematically and apply it to optimal export policies to reduce overall costs. The document also delves into planning and logistical aspects through a "stage transport" model (from production to warehouses and then to the consumer) and a "Location Problem" model to support reconstruction projects, taking into account available operating capacities. The research concludes by presenting a practical model for urban transport companies that aims to "minimize the time empty units travel" to the lowest possible level, using matrices of dimensions and distances between garages and loading and unloading locations to arrive at a daily work program that achieves maximum economic efficiency for the transport fleet.